THE INFLUENCE OF THE WORK ENVIRONMENT AND COMMUNICATION ON EMPLOYEE PERFORMANCE THROUGH TEAM WORK AS A MEDIATING VARIABLE AT DPUPR KARANGANYAR OFFICE - Pramesti, Bherliana Vanny; Dyah, Ida Aryati; Pawenang, Supawi; Kristiani, Endah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine the relationship between the work environment, communication on employee performance mediated by Team Work study at DPUPR Karanganyar office. The population in this study was 181 respondents. The sampling technique in this study uses a non-propability sampling approach with Saturation Sampling technique, which is a sampling technique using a total population of 181 employees. Based on the results of research that has been done, it can be concluded that direct influence without going through mediating variables of the work environment affects employee performance, communication affects employee performance, Team Work affects employee performance. While the influence of variables through work environment mediation variables on employee performance with Team Work mediation has a significant effect and communication variables on employee performance mediated by Team work has a significant effect. Keywords: Work Environment, Communication, Team Work, Employee Performance